Civil Society and Good Governance in Societies in Transition: the Case of Croatia - Vidačak, Igor (Array, 2006)
The paper deals with the legislative and policy framework that determines the Croatian civil society and its possibilities of contributing to enhancing good governance practices in the country, especially in the context of the civil dialogue and the European integration process. As the success of government action depends largely on the interaction of private sector and civil society, strengthening the partnership process between them can improve the social accountability and ensure more active civil participation in policy-making. Persistent endeavours from the late 1990s onwards on the part of both Government and CSOs to achieve a paradigm shift from opposition to cooperation resulted in considerable improvements of the legal and institutional environment for the development of civil society in Croatia. The adoption of new models of dialogue and cross-sector collaboration during the EU accession process should lead to the creation of the preconditions for introducing modern principles of good governance and promoting the Europeanization of the policy-making processes at all levels in Croatia.